Resolusi Konflik Sosial oleh Forum Komunikasi Pemolisian Masyarakat di Kepolisian Sektor Bukit Raya - Ilham Nur NG; Yusmar Yusuf; Swis Tantoro (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
The Bukit Raya Police Sector has a high population density and a low police-to-community ratio. The area has only 80 police officers, with 10 members of the Community Development Unit (Bimas). According to the Central Bureau of Statistics, the crime rate is the third highest in Pekanbaru City. To realise order and security, the police implemented community policing. This research aims to find out how the implementation strategy of community policing and what obstacles are experienced. The research method used is descriptive qualitative. The data used are primarily in the form of observations, interview results, photos and videos. Also secondary data such as crime statistics, population statistics, and research journals. Data collection using observation and in-depth interviews. While data analysis is; reduction, data analysis, and conclusion drawing. The results of this study are; a community policing implementation strategy and the formation of the Community Policing Communication Forum (FKPM) to coordinate activities related to community policing. While the obstacles faced are limited police members, a lack of certified Bhabinkamtibmas members, weak coordination, a weak understanding of community policing, and a limited budget.